Pengaruh Perlakuan Ekstraksi Terhadap Sifat Fisika dan Mekanika Papan Semen Berbahan Baku Tumbuhan Bamban (Donax canniformis) : The Effect of Extraction Treatment on the Physical and Mechanical Properties of Cement Boards Made from Bamban (Donax canniformis) - Luhan, Gimson; Santoso, Mahdi; Putra, Apri Wijaya; Supriyati, Wahyu; Christy, Eva Oktoberyani; Silvianingsih, Yosefin Ari; Yanciluk, Yanciluk (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2023)
Wood or lignocellulosic materials with high extractives are not recommended for making cement boards. Extraction of raw materials before the cement board manufacturing is a treatment carried out to address this issue. The aim of this research is to determine the influence of cold and hot water extraction treatment on Bamban particles on the quality of the cement boards. This research was conducted by immersion bamban particles on hot water (boiling at 100°C) for 3 hours. The mixture ratio between cement and bamban particles was 1.5:1 (w/w), and it was compressed for 1 hour at a pressure of 30 bar, followed by manual pressure (clamping) for 24 hours. The physical and mechanical properties of cement boards was conducted according to SNI 03-2104-1991 for wood-wool cement boards. The results of the study show that hot water extraction treatment has a very significant effect on the quality of the resulting cement boards.